2018
DOI: 10.1016/j.ygyno.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive hysterectomy surgery rates for endometrial cancer performed at National Comprehensive Cancer Network (NCCN) Centers

Abstract: At NCCN-designated centers, the MIS hysterectomy rate in EC is higher than the published national average, with low perioperative complications. Previously identified disparities of age, race, and BMI were not observed. A proposed MIS hysterectomy benchmark of >80% in EC care is feasible when performed at high volume centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 24 publications
3
44
0
1
Order By: Relevance
“…7 8 11 14-16 Bergstrom et al evaluated the rates of minimally invasive surgery for endometrial cancer at high-volume National Comprehensive Cancer Network centers and concluded that disparities in age, race, and body mass index seen in studies based on national databases were not observed at these centers, and the rates of minimally invasive surgery at these centers were higher than the national average, all while having low perioperative complications. 14 In the landmark LAP2 study, Walker et al demonstrated the safety and feasibility of minimally invasive surgery in endometrial cancer, without compromise to oncologic outcomes in these patients. 7 8 These patients had less postoperative pain, shorter recovery periods, and shorter length of hospital stay, without an increase in rates of complications, intraoperative injuries, or compromise to survival.…”
Section: Discussionmentioning
confidence: 99%
“…7 8 11 14-16 Bergstrom et al evaluated the rates of minimally invasive surgery for endometrial cancer at high-volume National Comprehensive Cancer Network centers and concluded that disparities in age, race, and body mass index seen in studies based on national databases were not observed at these centers, and the rates of minimally invasive surgery at these centers were higher than the national average, all while having low perioperative complications. 14 In the landmark LAP2 study, Walker et al demonstrated the safety and feasibility of minimally invasive surgery in endometrial cancer, without compromise to oncologic outcomes in these patients. 7 8 These patients had less postoperative pain, shorter recovery periods, and shorter length of hospital stay, without an increase in rates of complications, intraoperative injuries, or compromise to survival.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are characterized by low perioperative complications with higher weight/BMI as barriers to performance. A proposed MIS hysterectomy benchmark of >80 % in endometrial cancer care is feasible when performed at high-volume centers with gynecologic oncologists [6].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical cytoreduction remains paramount in the treatment of early-stage and advanced endometrial cancer. MIS was approved as a quality measure by the Society of Gynecologic Oncology (SGO) in 2014 and incorporated into the National Comprehensive Cancer Network's (NCCN) guidelines in 2017 [6,7]. Globally, a recent U.S. Centers for Disease Control (CDC) study demonstrated that endometrial cancer rates increased in 26 of the 43 countries, with South Africa and several countries in Asia showing the largest increase [8].…”
Section: Introductionmentioning
confidence: 99%
“…The minimally invasive can be performed to endometrial cancer safely with the utilization of the retrieval bag through a vagina to limit tissue fragmentation within a packet. 3 This case was selected for the closed-entry procedure with general Veress needle technique; the two attempts were successful for VN insertion followed by the creation of pneumoperitoneum at a pressure of 15 mm Hg, the VN was removed. There is no accepted universal definition of failed closed-entry.…”
Section: Discussionmentioning
confidence: 99%